Spoiled Children: Problem dan Solusi (THUFULA, 2017)
Abstract:SPOILED CHILDREN: PROBLEM AND SOLUTIONS. The definitionof a spoiled child may be almost the same as a child who is overly protectedby his parents. But is it true that spoiled is synonymous with 'overprotected'?This article attempts to examine spoiled children from apsychological point of view, beginning with the definition or characteristicsof children with spoiled categories, future consequences, causal factors,prevention, and solutions if it is already happen. Some parents do notrealize that they have spoiled their child. This becomes a problem thatmust be solved. Spoiled child is a self-centered child, he does not care aboutthe needs of others. Being focused on him, he demands that everything befulfilled now and can not wait. Unconsciously by the parents actually thebehavior is caused by permissive parents because of the condition ofparents who are tired, working, and looking for easy. For the sake of thechild's future this should be prevented by the assertiveness and consistencyof the parents themselves.Abstrak: Definisi anak yang manja mungkin hampir sama dengan anakyang terlalu dilindungi oleh orang tuanya. Namun apakah benar bahwamanja identik dengan ‘over-protected?’ Artikel ini mencoba menelaahanak manja dari sudut psikologi, dimulai dari definisi atau ciri-ciri anakdengan kategori manja, akibat di masa datang, faktor penyebab,pencegahan, dan solusi jika itu sudah terjadi. Sebagian orang tua tidakmenyadari bahwa mereka telah memanjakan anak mereka. Ini menjadimenjadi problem yang harus dicarikan jalan keluarnya. Anak manjaadalah anak yang terpusat pada dirinya sendiri, ia tidak peduli dengankebutuhan orang lain. Karena terpusat pada dirinya, ia menuntut segalasesuatu terpenuhi sekarang dan tidak bisa menunggu. Tanpa disadarioleh orang tua sebenarnya perilaku itu disebabkan oleh orang tua yangpermisif karena kondisi orang tua yang lelah, bekerja, dan mencarimudahnya. Demi masa depan anak maka hal ini harus dicegah dengansikap ketegasan dan kekonsistenan dari orang tua itu sendiri.